2010
DOI: 10.1093/humupd/dmq004
|View full text |Cite
|
Sign up to set email alerts
|

The patients' perspective on fertility care: a systematic review

Abstract: Fertility patients have 'human needs' besides their need for medical care. Evidence on PCRM is available but significant methodological limitations call for the development and validation of a European questionnaire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
175
2
11

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(198 citation statements)
references
References 69 publications
10
175
2
11
Order By: Relevance
“…67,83 However, there is now a body of evidence that elucidates some of the psychological and social aspects of infertility for men. 3 While the research has been undertaken in diverse settings using varied designs, sampling and recruitment strategies, and data sources, there is considerable consistency among the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…67,83 However, there is now a body of evidence that elucidates some of the psychological and social aspects of infertility for men. 3 While the research has been undertaken in diverse settings using varied designs, sampling and recruitment strategies, and data sources, there is considerable consistency among the findings.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of research concerning patients' perspectives on fertility care 67 found that very few studies (3/51) had focused specifically on men's experiences. The main findings were not disaggregated to distinguish men's accounts, but it was argued that the relevant dimensions applied to all infertility treatment consumers and included the following parameters: access to services; respect for values, choices and needs; continuity and coordination of care; appropriate information and education; physical comfort; support to reduce anxiety; and involvement of partners.…”
Section: Male Experiences Of Infertility Treatmentmentioning
confidence: 99%
“…Participants also felt that communication with clinics was better than in the UK, often with direct and readily available access to the clinician leading their care. Many of these factors have been identified as key components of 'patient-centred fertility care' generally (Dancet et al, 2010;Dancet et al, 2011;Redshaw, Hockley, & Davidson, 2007;Schmidt et al, 2003). A systematic review of patients' perspectives of fertility care concluded that fertility patients 'want to be treated like human beings with a need for: medical skills, respect, coordination, accessibility, information, comfort, support, partner involvement and a good attitude of and relationship with fertility clinic staff' (Dancet et al, 2010, p. 467).…”
Section: It Was a Bit More Daunting There's The Language And Cyrillimentioning
confidence: 99%
“…Participants described crossborder treatment as often characterized by uncertainty. Studies of the infertility treatment experience generally highlight this as a process typified by doubt and anxiety (Dancet et al, 2010;Franklin, 1997;Thompson, 2005;Throsby, 2004). The uncertainty associated with cross-border treatment had a particular set of inflections due to its transnational dimension.…”
Section: It Was a Bit More Daunting There's The Language And Cyrillimentioning
confidence: 99%
“…Patient-oriented care is a trend in health care established to prevent condescending relationships from medical personnel towards patients (Dancet et al 2010). The ultimate objective is to foster more informed and carefully made choices by patients.…”
mentioning
confidence: 99%